Data of in vitro synthesized dsRNAs on growth and development of helicoverpa armigera - Chikate, Y. R.; Dawkar, V. V.; Barbole, R. S.; Tilak, P. V.; Gupta, V. S.; Giri, A. P. (Data in Brief, 2016)
The data presented in this article is related to the research article "RNAi of selected candidate genes interrupts growth and development of Helicoverpa armigera" (Chikate et al., 2016) [1]. RNA interference (RNAi) is emerging as a potent insect pest control strategy over current methods and their resistance by pest. In this study we tested 15 different in vitro synthesized dsRNAs for gene silencing in Helicoverpa armigera. These dsRNAs were specific against H. armigera enzymes/proteins such as proteases like trypsins (HaTry2, 3, 4 and 6), chymotrypsin (HaChy4) and cysteine proteases such as cathepsin (HaCATHL); glutathione S-transferases (HaGST1a, 6 and 8); esterases (HaAce4, HaJHE); catalase (HaCAT); super-oxide-dismutase (HaCu/ZnSOD); fatty acid binding protein (HaFabp) and chitin deacetylase (HaCda5b). These dsRNAs were fed to second instar larvae at an optimized dose (60 μg/day) for 3 days separately. Effects of dsRNA feeding were observed in terms of larval mass gain, percentage mortality and phenotypic abnormalities in later developmental stages of H. armigera. These findings might provide potential new candidates for designing sequence-specific dsRNA as pesticide in crop protection.

Data on changes in the fatty acid composition during fruit development and ripening of three mango cultivars (Alphonso, Pairi and Kent) varying in lactone content - Deshpande, A. B.; Chidley, H. G.; Oak, P. S.; Pujari, K. H.; Giri, A. P.; Gupta, V. S. (Data in Brief, 2016)
Data in this article presents fatty acid composition of three mango cultivars; Alphonso, Pairi and Kent through fruit development and ripening. Change in the ω-6 and ω-3 fatty acids level during mango fruit development and ripening is depicted. Also, data on aroma volatile ‘lactones’ composition from pulp and skin tissues of these cultivars at their ripe stage, respectively is provided. Statistical data is also shown, which correlates modulation in lactone content with that of fatty acid composition and content during fruit development and ripening in all the three mango cultivars.

Diversity of arsenic resistant bacteria from Lonar lake: A meteorite impact alkaline crater lake in Indi - Bagade, A. V.; Paul, D.; Rikame, T.; Giri, A. P.; Dhotre, D.; Pawar, S.; Kodam, K. (Arsenic Research and Global Sustainability - Proceedings of the 6th International Congress on Arsenic in the Environment, AS 2016, 2016)
Lonar lake known for its meteorite impact origin and highly alkaline environment harbors a plethora of diverse organisms. Arsenic transforming microbe diversity from Lonar remains unexplored. We attempted to explore the microorganisms causing arsenic transformation using culture-dependent and independent approaches. Amongst the 67 microbes isolated, Bacillus infantis L4-18 and Bacillus solimangrovi L4-7b could oxidise 15 mM arsenite in 8 days. None of the cultures could reduce arsenate. All the other isolates resisted 2 mM arsenic. In the culture independent approach, microbial diversity revealed Bacteroides (41.9%), followed by Proteobacteria (17.9%), Firmicutes (14.2%), Actinobacteria (13.9%), occurring in the Lonar sediment sample. This study provides foundation to study microbial arsenic biogeochemical cycle along with other biochemical cycles and microbial function in Lonar lake eco system.

Data on metabolic profiling of spongy tissue disorder in Mangifera indica cv. Alphonso - Oak, P. S.; Deshpande, A. B.; Pujari, K. H.; Prabhudesai, S. S.; Giri, A. P.; Gupta, V. S. (Data in Brief, 2019)
Data in this article presents aroma volatiles and fatty acids composition of mesocarp specific malady namely spongy tissue disorder in Mangifera indica cv. Alphonso. Quantitative changes in various aroma volatile compound classes as well as saturated and unsaturated fatty acids in spongy tissue vis-à-vis healthy mesocarp have been analyzed throughout the development of the disorder. Statistical data analysis correlates the dynamic changes in the aroma volatiles composition to that of the modulation in the fatty acids profile.